2012
DOI: 10.2967/jnumed.112.104588
|View full text |Cite
|
Sign up to set email alerts
|

Altered GABAA Receptor Density and Unaltered Blood–Brain Barrier Transport in a Kainate Model of Epilepsy: An In Vivo Study Using 11C-Flumazenil and PET

Abstract: The aim of the present study was to investigate if flumazenil blood-brain barrier transport and binding to the benzodiazepine site on the g-aminobutyric acid A (GABA A ) receptor complex is altered in an experimental model of epilepsy and subsequently to study if changes in P-glycoprotein (P-gp)-mediated efflux of flumazenil at the blood-brain barrier may confound interpretation of 11 C-flumazenil PET in epilepsy. Methods: The transport of flumazenil across the blood-brain barrier and the binding to the benzod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 42 publications
3
18
1
Order By: Relevance
“…In addition, BP ND was not affected significantly by P-gp inhibition, which is also in line with animal studies showing that tariquidar had no effect on [ 11 C]flumazenil binding to the GABA A receptor in both naïve and kainate-treated rats. 21 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, BP ND was not affected significantly by P-gp inhibition, which is also in line with animal studies showing that tariquidar had no effect on [ 11 C]flumazenil binding to the GABA A receptor in both naïve and kainate-treated rats. 21 …”
Section: Discussionmentioning
confidence: 99%
“…This reduction in GABAergic neurotransmission may be caused by any or all of the following: loss of GABAergic interneurons, loss of GABA A receptors, or changes to GABA A receptor subunits, leading to alterations in receptor properties [2], [3], [4] and needs to be further investigated. Previous animal and human studies have shown decreased GABA A /central benzodiazepine receptor (GABA A /cBZR) density in structures important to seizure generation in the mesial temporal lobe [5], [6], [7], [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Syvänen [253] determined the GABA A receptor density, B max , in rat brain using four doses (between 4 μg and 400 μg) of As long as the tracer kinetics can be considered linear (which is usually a valid assumption) a sufficiently comprehensive compartmental model (with a sufficient number of compartments) will be able to describe any given system. Increasing the number of compartments suffi ciently, one can even model diffusive processes (which inherently imply the presence of concentration gradients).…”
Section: Estimation Of Receptor-binding Parameters In Animalsmentioning
confidence: 99%
“…For example, Syvänen [253] determined the GABA A receptor density, B max , in rat brain using four doses (between 4 μg and 400 μg) of reported, while K D remained unchanged [253] .…”
Section: Estimation Of Receptor-binding Parameters In Animalsmentioning
confidence: 99%